The iBRA (implant breast reconstruction evaluation) study: protocol for a prospective multi-centre cohort study to inform the feasibility, design and conduct of a pragmatic randomised clinical trial comparing new techniques of implant-based breast reconstruction. Issue 1 (December 2016) - Potter, Shelley; Conroy, Elizabeth; Williamson, Paula; Thrush, Steven; Whisker, Lisa; Skillman, Joanna; Barnes, Nicola; Cutress, Ramsey; Teasdale, Elizabeth; Mills, Nicola; Mylvaganam, Senthurun; Branford, Olivier; et al.
Abstract Background Implant-based breast reconstruction (IBBR) is the most commonly performed reconstructive procedure in the UK. The introduction of techniques to augment the subpectoral pocket has revolutionised the procedure, but there is a lack of high-quality outcome data to describe the safety or effectiveness of these techniques. Randomised controlled trials (RCTs) are the best way of comparing treatments, but surgical RCTs are challenging. The iBRA (implant breast reconstruction evaluation) study aims to determine the feasibility, design and conduct of a pragmatic RCT to examine the effectiveness of approaches to IBBR. Methods/design The iBRA study is a trainee-led research collaborative project with four phases:Phase 1 – a national practice questionnaire (NPQ) to survey current practice Phase 2 – a multi-centre prospective cohort study of patients undergoing IBBR to evaluate the clinical and patient-reported outcomes Phase 3– an IBBR-RCT acceptability survey and qualitative work to explore patients' and surgeons' views of proposed trial designs and candidate outcomes. Phase 4 – phases 1 to 3 will inform the design and conduct of the future RCT All centres offering IBBR will be encouraged to participate by the breast and plastic surgical professional associations (Association of Breast Surgery and British Association of Plastic Reconstructive and Aesthetic Surgeons). Data collected will inform the feasibility of undertaking an RCT by defining current practice and exploring issues surrounding recruitment, selection of comparator arms, choice of primary outcome, sample size, selection criteria, trial conduct, methods of data collection and feasibility of using the trainee collaborative model to recruit patients and collect data. Discussion The preliminary work undertaken within the iBRA study will determine the feasibility, design and conduct of a definitive RCT in IBBR. It will work with the trainee collaborative to build capacity by creating an infrastructure of research-active breast and plastic surgeons which will facilitate future high-quality research that will ultimately improve outcomes for all women seeking reconstructive surgery. Trial registration ISRCTN37664281